Development of an Android-Based E-Module on Hypnoprenatal Material for Diploma III Midwifery Students - Sari Wahyuni; Nurul Komariah (Institute of Computer Science (IOCS), 2026)
Mobile technology has become increasingly important in health professions education, yet midwifery learning in Indonesia still relies largely on printed modules and conventional lectures. Hypnoprenatal is a relaxation technique that has been reported in the literature as a complementary approach to reduce antenatal anxiety and fear of childbirth; however, digital instructional resources covering this topic for midwifery students remain limited. This study aimed to develop an Android-based hypnoprenatal e-module for Diploma III Midwifery students and to assess its feasibility as a learning medium, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) as the research and development (R&D) framework. Methods: Feasibility was evaluated by two material experts, one media expert, one lecturer, and 20 fourth-semester students through validated five-point Likert-scale questionnaires. Responses were analyzed descriptively by calculating the percentage of agreement for each respondent group, which was then interpreted against a predetermined feasibility category scale (e.g., 81–100% =